A self-monitoring approach for evaluating the effect of 3 weeks of high-intensity training in patients with type 2 diabetes mellitus. An intervention study. (March 2019) - Dissing, Anne-Mette; Johansen, Mette D.; Pilegaard, Morten; Hejlesen, Ole
Highlights: Simple self-testing methods could be used to measure improvements after 8 times of HIT. HIT improved 2 h blood glucose concentration, diastolic blood pressure and weight. HIT was well-tolerated, and no adverse events were recorded.